Cost Efficiency of Malaysian Oleochemical Enterprises: A Non-parametric Frontier Analysis Evidence - O. A. Bushara, Mohamed; G. Mohayidin, Mohd. (Gezira Journal of Agricultural Science, 2021)
The objectives of the paper are two-folds. First the cost efficiency measure was decomposed into technical and allocative efficiency in Malaysian oleochemical industry. This is undertaken with the explicit aim of evaluating the competitiveness of this industry since early 1990s, The data used were an incomplete panel of annual observations on 12 firms, comprising 80% of the operating oleochemical films which operated between 1990-1996. The second objective of this paper is to show that the application of the deterministic Data Envelopment Analysis (DEA) frontier model could provide good explanation regarding economic relationships over time. The mean cost-inefficiencies of Malaysian oleochemical enterprises for 7 different years (1996- 1990) tended to increase from 1991 to 1996. The mean cost- inefficiencies increased slowly and slightly up to 1995 when there was a sharp decrease. The major contributor to this inefficiency was allocative inefficiency.